Masa Depan Cerah Bersama SMART Kids: Save Money, Avoid Risk, Master Technology - Bimantoro, M Rangga; Mutmainah, Shoffia Ashriana Nuur; Rizqy, Gilang Amukti; Binthalib, Fadila; Putri, Septi Ameilia; Abesti, Yanu Aditya; Aulia, Syahrani; Yogatama, Arya Rizky; Jannah, Choerunnisa Miftahul; Rahmadansyah, Muhammad Alfatur; Mulyono, Mulyono (Universitas Muhammadiyah Yogyakarta, 2025)
The use of information and communication technology (ICT), especially gadgets, has become an important part of everyday life, but excessive use can have a negative impact on children's development. In Dusun Gatak, many young people, especially children, especially at the elementary school level, are exposed to the use of gadgets without adequate parental supervision and can interfere with their concentration in learning, social development, and physical and mental health. This community service program aims to inform children about the potential risks of excessive gadget use and how to avoid the risks that will occur. This program is an alternative in teaching children in Dusun Gatak to save money to manage money for emergency needs or to buy desired items. This program also aims to educate the importance of using information and communication technology in the scope of education in this modern era. The methods used in this service include socialization to children of SDN 2 Kopen about the negative impacts of gadgets, savings training, and ANBK training activities that directly involve children. The main program that has been implemented is the socialization of the dangers of gadgets for children of SDN 2 Kopen, which is followed by several supporting programs, such as a wall magazine competition as a place for creativity, socialization of the importance of saving, ICT teaching that utilizes technology positively, guidance for TPA children, as well as community service activities, integrated health posts, and healthy gymnastics. The results of this service show that elementary school children in Gatak Hamlet now better understand the negative impacts of excessive gadget use, such as impaired concentration in learning and health problems, and are more disciplined in limiting the time they spend playing gadgets. The increase in children's participation in saving money is also very enthusiastic and has increased significantly. Increased children's confidence with more than 80% able to operate the basic features of Microsoft Word independently, as well as showing increased readiness in facing computer-based examinations. Overall, the program succeeded in providing a better understanding for the children of SDN 2 Kopen in Gatak village, and can encourage them to become a younger generation that is more active in positive physical and social activities